STUDI EKSPERIMEN PENGARUH KUAT ARUS TERHADAP KEKUATAN TARIK DAN KEKERASAN HASIL LASAN LOGAM PIPA ALUMINIUM SERI 5000 (AlMg5) - Ali Achmadi (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2015)
Welding technology is one part that can not be separated in manufacturing technology. In general,welding can be interpreted as a metallurgical bond in a metal or alloy metal connection which iscarried out when the metal is liquid. Now welding is the implementation of a very important job inproduction technology with metal raw materials. In this study aims to determine how the influence ofstrong currents on mechanical properties in MIG welding. that is by changing the welding currentstrength of 70 A, 90 A and 110 A and using a reverse polarity DC welding machine. After weldingwith varying currents, tensile and hardness testing are carried out. From these stages it will be knownthe extent of the strong influence of the flow of MIG welding results. The test results show that weldingwith a strong current of 70 A has the highest average tensile strength compared to a current strengthof 90 A and 110 A that is equal to 121.25 N / mm2. Furthermore, for hardness testing, the highesthardness data is found on the welding metal with a strong current of 70 A with a value of 96.6 HRB.From the results of tensile testing and hardness testing, the current strength factor greatly influencesthe results of welds (tensile strength and hardness). Here the 70 A strong current can produce betterwelding strength than 90 A and 110 A.